The model analysis of Malaysia’s natural rubber demand towards economic growth / Nur Syamimi Mohd Zaki - Mohd Zaki, Nur Syamimi (Faculty of Plantation and Agrotechnology, 2018)
Malaysia becoming top list of major producer and exporter of natural rubber in the past few decades but recently, the export demands of natural rubber from Malaysia’s country keep decreasing year by year and this situation give a lot of worried to the agriculture producer. The objective of this study is to identify the factor affecting natural rubber export and the relationship between natural rubber exports with economic growth. By using the annual data from period 1987 until 2017, it uses natural rubber export and Malaysia’s Gross Domestic Product (GDP) as independent variables and monthly data from year 2010 until 2017 for the natural rubber prices, synthetic rubber price, exchange rate and industrial production index as independent variables and export of natural rubber as dependent variable. This study also test whether there have been long run relationship between natural rubber export and all the variables. The Augmented Dickey-Fuller test shows that all the data are stationary at first difference. The Johansen co-integration test revealed that synthetic rubber price, and exchange rate a positive significant effect on export for the natural rubber while natural rubber price and industrial production index have negative significant effect on export of natural rubber. All the variables are significant at one per cent level of significance. In the short run, the results revealed that only natural rubber price has significant effect on natural rubber export. Meanwhile, Granger Causality Test shown that Malaysia’s Gross Domestic Product leads to natural rubber export and the results are significant. Therefore, several recommendations such as policy implementation, liberalization and export market strategy can be implemented to increase the natural rubber export.